Do fine needle aspirate cytomorphological features correlate with positron emission tomography findings of metastatic non‐small cell lung carcinoma in lymph nodes? - Kianoosh Keyhanian; Harmanjatinder S. Sekhon (Cancer Medicine, 2023)
Abstract Background Our objective was to correlate cytomorphological features of metastatic non‐small cell lung carcinoma (mNSCLC) with maximal standardized uptake value (mSUV) of positron emission tomography (PET) in Lymph nodes (LNs). Methods Positive cytology slides of 114 LNs were reviewed from 100 patients with mNSCLC who had undergone PET study. Student's t‐test was used for statistical comparisons. Results Mean patients' age: 68.5, 54% male. LNs locations were: mediastinum: 99, lung hilum: 13, peribronchial: 1, axilla: 1. Final diagnoses were: Adenocarcinoma: 86, squamous cell carcinoma: 28 LNs. Within the adenocarcinoma subgroup, histological patterns correlate with mSUV. Acinar and papillary patterns were associated with significantly lower mSUVs (mean ± standard error (SE): 7.9 ± 0.9 and 9.2 ± 0.8, respectively) than solid pattern (13.0 ± 1.2; p values: 0.001 and 0.009, respectively). Similar difference exists between patterns associated with low‐ and high‐grade adenocarcinoma (Mean ± SE: 9.2 ± 0.8 and 12.0 ± 1.0, respectively. p value: 0.02). Interestingly, micropapillary pattern was associated with the lowest mSUV amongst all patterns (Mean ± SE: 5.4 ± 1.1). Other features that correlated with higher mSUV were necrosis, moderate/severe nuclear atypia, lower lymphoid tissue yield, and contralateral LN involvement. Conclusions In LNs with mNSCLC, certain cytomorphological features are associated with higher mSUV. Micropapillary, a pattern considered as high‐grade, is associated with lower SUV values; hence, a lower SUV threshold may raise concern for metastasis. Although high SUV is associated with LN metastasis, lower SUV levels in certain adenocarcinomas suggest correlation with clinical and morphological characteristics could be valuable in tailoring therapeutic management.